2019
DOI: 10.48550/arxiv.1909.01940
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Can we trust deep learning models diagnosis? The impact of domain shift in chest radiograph classification

Abstract: While deep learning models become more widespread, their ability to handle unseen data and generalize for any scenario is yet to be challenged. In medical imaging, there is a high heterogeneity of distributions among images based on the equipment that generate them and their parametrization. This heterogeneity triggers a common issue in machine learning called domain shift, which represents the difference between the training data distribution and the distribution of where a model is employed. A high domain sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…We hypothesized a distributional difference in noise and texture characteristics between the data sources due to diverse conditions in X-ray equipment and their configurations for generating the images. We based our hypothesis on the recent findings (Pooch et al, 2019;Yao et al, 2019), which implicitly showed the existence of some characteristic differences between these data sources. This work has developed an explicit method to show the characteristic differences between the data sources.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized a distributional difference in noise and texture characteristics between the data sources due to diverse conditions in X-ray equipment and their configurations for generating the images. We based our hypothesis on the recent findings (Pooch et al, 2019;Yao et al, 2019), which implicitly showed the existence of some characteristic differences between these data sources. This work has developed an explicit method to show the characteristic differences between the data sources.…”
Section: Discussionmentioning
confidence: 99%
“…1-2, one can observe that there are clear distribution shifts in these medical imaging data. However, many conventional machine learning methods ignore this problem, which would lead to performance degradation [26], [30]. Recently, domain adaptation has attracted increasing interests and attention of researchers, and become an important research topic in machine learning based medical image analysis [22], [31]- [33].…”
Section: A Domain Shift In Medical Image Analysismentioning
confidence: 99%
“…The domain shift across different hospital settings is the main obstacle in transferring deep learning models into clinical practice [11]. It can result in poor generalization and decreased accuracy [4].…”
Section: Model Performance On External Test Setmentioning
confidence: 99%